Whole-Exome Sequencing Identifies a Novel POLG Frameshift Variant in an Adult Patient Presenting with Progressive External Ophthalmoplegia and Mitochondrial DNA Depletion - Justin Kurtz; Joseph Americo Fernandes; Mahesh Mansukhani; William C. Copeland; Ali B. Naini (Case Reports in Genetics, 2021)
Mitochondrial DNA (mtDNA) depletion syndromes are a group of autosomal recessive disorders associated with a spectrum of clinical diseases, which include progressive external ophthalmoplegia (PEO). They are caused by variants in nuclear DNA (nDNA) encoded genes, and the gene that encodes for mtDNA polymerase gamma (POLG) is commonly involved. A splice-site mutation in POLG, c.3104+3A > T, was previously identified in three families with findings of PEO, and studies demonstrated this variant to result in skipping of exon 19. Here, we report a 57-year-old female who presented with ophthalmoplegia, ptosis, muscle weakness, and exercise intolerance with a subsequent muscle biopsy demonstrating mitochondrial myopathy on histopathologic evaluation and multiple mtDNA deletions by southern blot analysis. Whole-exome sequencing identified the previously characterized c. 3104+3A > T splice-site mutation in compound heterozygosity with a novel frameshift variant, p.Gly23Serfs∗236 (c.67_88del). mtDNA copy number analysis performed on the patient’s muscle showed mtDNA depletion, as expected in a patient with biallelic pathogenic mutations in POLG. This is the first reported case with POLG p.Gly23Serfs∗236, discovered in a patient presenting with features of PEO.